Polymyxin E Induces Rapid Paenibacillus polymyxa Death by Damaging Cell Membrane while Ca2+ Can Protect Cells from Damage. - Zhiliang Yu; Yuanning Cai; Wangrong Qin; Jianxun Lin; Juanping Qiu (PLoS ONE, 2015)
Polymyxin E, produced by Paenibacillus polymyxa, is an important antibiotic normally against Gram-negative pathogens. In this study, we found that polymyxin E can kill its producer P. polymyxa, a Gram-positive bacterium, by disrupting its cell membrane. Membrane damage was clearly revealed by detecting the leakage of intracellular molecules. The observation using scanning electron microscopy also supported that polymyxin E can destroy the cell membrane and cause an extensive cell surface alteration. On the other hand, divalent cations can give protection against polymyxin E. Compared with Mg2+, Ca2+ can more effectively alleviate polymyxin E-induced damage to the cell membrane, thus remarkably increasing the P. polymyxa survival. Our findings would shed light on a not yet described bactericidal mechanism of polymyxin E against Gram-positive bacteria and more importantly the nature of limited fermentation output of polymyxin E from P. polymyxa.